2022
DOI: 10.1097/tp.0000000000004271
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Sorafenib for Recurrent Hepatocellular Carcinoma After Liver Transplantation in the Era of Combined and Sequential Treatments

Abstract: Background. Sorafenib and other tyrosine kinase inhibitors are the current standard of care for hepatocellular carcinoma (HCC) recurring after liver transplantation (LT). Sorafenib is sometimes regarded as a scarcely effective treatment in this setting because of some studies showing a short overall survival (OS) indirectly compared with historical series of nontransplanted patients. Additional data from multicenter prospective studies are needed before drawing definite conclusions. Methods. Retrospective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…With these preconditions, TKI monotherapy seems to be outdated, but it still assumes a central role in the therapeutic scenario for patients with advanced HCC and contraindications to ICIs [35] or solid organ recipients [36]; furthermore, recent studies seem to highlight that the etiology of underling liver disease could influence the response to different first-line therapies [37].…”
Section: Discussionmentioning
confidence: 99%
“…With these preconditions, TKI monotherapy seems to be outdated, but it still assumes a central role in the therapeutic scenario for patients with advanced HCC and contraindications to ICIs [35] or solid organ recipients [36]; furthermore, recent studies seem to highlight that the etiology of underling liver disease could influence the response to different first-line therapies [37].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 26 patients who underwent sorafenib treatment followed by LT, 15 were alive without disease recurrence at 5 years. Another recent study found that post-LT patients with progression of HCC who received adjuvant sorafenib had median OS of 18 months, which is considerably improved from previous estimates [36]. Antiangiogenic agents are often used in conjunction with ICIs and have been shown to have reasonably good outcomes with cases of post-LT HCC recurrence [37–40].…”
Section: Downstaging To Transplantmentioning
confidence: 93%
“…The incidence of intrahepatic metastasis and multicentric recurrent HCC was 59.4% and 27.5%, respectively, which were accompanied by loss of heterozygosity (63.8%) and microsatellite instability (30.0%) between primary and recurrent tumors[ 34 ]. Concerning previously unidentified circulating tumor cells or preexisting metastasis caused by the current technology that contribute to extrahepatic relapse, metastatic tumor lesions in the graft are originally formed from circulating cells or extrahepatic locales, providing a greater potential for biological advancement[ 35 ].…”
Section: Mechamism Of Recurrent Hccmentioning
confidence: 99%
“…Sequential sorafenib treatments are similarly common in recurrent HCC patients following LT. These treatments improve OS compared to non-LT treatments and do not suppress systemic treatments with concurrent antirejection strategy[ 35 ]. Treatment with sorafenib and TACE was associated with a higher 5-year OS and PFS compared to those treated with TACE alone in patients with recurrent intermediate-stage HCC and lesions positive for MVI, but patients with MVI-negative lesions did not show a survival benefit from combined therapy[ 114 ].…”
Section: Sorafenibmentioning
confidence: 99%